The role of Kurdish women's literature in the western mountainous region in the centuries (4-5K/10-11AD) - Jabar, Asst.L.Sarko Naji (Sulaimani Journal for Humanities, 2026)
Women's play has played an important role in the Kurdish society and participated in the public works of that society Many of the years have neglected the role of women in various fields, but none of the possible fields that played in the role of Kurdish women in history is literature. In the Kurdish society, women are known from the beginning, especially poetry. The words open the opportunity for Kurdish literature, women's rights to the side of men, according to the curse of some scholars and literary critics, promising women's participation Kurdishness in Literature towards Laughter, Taking a Look at the Regions of the Qur'an (4-5m/10-11m) (Western Mountain Region) opens up important opportunities for women's participation in books Kurdish Poetry This search is aimed at expressions around poets such as (Daya Tawrezi Hawrami, Jalala Khanum Loristani, Rihan Khanum Loristani, Fatemeh Loray Goran, Liza Khanum Jaf, Khatoo May Zard, Daya Khazani Sargati) where possible التحدث. The birth of the Kurdish language and the Hurami language is the driving force behind the Kurdish literary revolution, as discovered the fact that it was only after the Islamic conquests that Kurdish women before the state were created The latter is active in the book of poetry with its special character. The wisdom of the Kurdish authorities such as Al-Hasnawiyun and Bani Annaz in the region through this al-Fitr is one of the reasons for the extensive participation of women in the book of Kurdish poetry These authorities learned the Kurdish woman from her patriotic courage in poetry. Now, by virtue of this strength, the Kurdish woman learns from her patriotic courage in poetry, but it leads us to believe that the existence of Kurdish strength is not based on appearance The Woman's Period. Thus, to express the power and opportunities of women in the Irsani religion is the last important part of the research, but the fans are the guarantors of the Irsani religion Kurdish.
Keywords: Role of Women; History of Kurdish Literature; Western Mountain Region; Yarsan Religion